Pengaruh Tingkat Kecemasan Penyelesaian Skripsi Terhadap Aktivitas Sholat Tahajud Mahasiswa Prodi PAI IAINU Kebumen - Novianty Putri Pramita; Mustajab Mustajab; Atim Rinawati (IAINU Kebumen, 2023)
The completion of the thesis on the activities of the tahajjud prayer for the students of the PAI IAINU Kebumen Study Program for the Academic Year 2021-2022. This research uses a quantitative research approach, the design used is Product Moment correlation analysis, the object of this research is the influence of the anxiety level of thesis completion on tahajjud prayer activities in IAINU Kebumen students, data analysis using Product Moment Analysis. With the population in this study as many as 260 students from IAINU Kebumen in the PAI A Study Program Class of 2021-2022. by taking a sample of 72 students, with a systematic random sampling technique (Systematic Random Sampling). Based on the results of the research using the correlation hypothesis test, it shows that there is no influence of anxiety levels on tahajjud prayer activities in PAI students at IAINU Kebumen Academic Year 2021-2022, this result is evidenced by the value of Rxy or R count = -0.0599 < rtable 0, 0235, from the correlation between the level of anxiety of completing scripts on tahajjud prayer activities in PAI IAINU Kebumen students, the category is very weak.